2019
DOI: 10.5051/jpis.2019.49.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Bone healing dynamics associated with 3 implants with different surfaces: histologic and histomorphometric analyses in dogs

Abstract: Purpose This study evaluated differences in bone healing and remodeling among 3 implants with different surfaces: sandblasting and large-grit acid etching (SLA; IS-III Active ® ), SLA with hydroxyapatite nanocoating (IS-III Bioactive ® ), and SLA stored in sodium chloride solution (SLActive ® ). Methods The mandibular second, third, and fourth premolars of 9 dogs were extracted. After 4 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 30 publications
5
30
0
Order By: Relevance
“…By April 2020, a total of 128 studies had been gathered and subsequently assessed by the reviewers. From these, 92 studies were removed due to their being in vitro trials, duplicates, systematic reviews, or irrelevant, leaving a total of 30 studies: 27 were carried out on animals [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] and 3 on humans [ 23 , 24 , 25 ] ( Figure 2 “Flowchart”). Table 3 and Table 4 provide a general description of the details of each study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By April 2020, a total of 128 studies had been gathered and subsequently assessed by the reviewers. From these, 92 studies were removed due to their being in vitro trials, duplicates, systematic reviews, or irrelevant, leaving a total of 30 studies: 27 were carried out on animals [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] and 3 on humans [ 23 , 24 , 25 ] ( Figure 2 “Flowchart”). Table 3 and Table 4 provide a general description of the details of each study.…”
Section: Resultsmentioning
confidence: 99%
“…In animal studies, ISQ was reported by 2 studies [ 26 , 27 ], both of which showed an increase when HA and alumina bioactive surfaces were used. BIC was reported in 11 studies [ 28 , 29 , 30 , 32 , 33 , 35 , 36 , 37 , 38 , 39 , 40 , 42 , 43 , 44 , 45 , 46 , 49 , 50 , 51 ]; BIC and BA together—5 studies [ 28 , 32 , 35 , 36 , 39 ]; RTT was reported in a study using rat tibiae where machined Ti surfaces and HA coated surfaces were compared [ 48 ]; RE (microcomputed tomography) is reported in 2 studies [ 31 , 34 ], SF—in one study [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Unlike preclinical studies of chemically modified SLA implants and HA-coated implants increasing osseointegration at the early bone healing stage [ 20 ], this clinical study failed to confirm the clinical benefits of HA-coated implants or chemically modified SLA implants compared to conventional SLA implants. The effect of implant surface modification might be masked by inclusion criteria such as sufficient bone quantity and good bone quality for this study.…”
Section: Discussionmentioning
confidence: 78%
“…The study design was a three-arm randomized controlled trial. Three different types of implants were used in this study, as follows: SLActive bone level implant (Institut Straumann AG, Basel, Switzerland; surface roughness (Ra) = approximately 1.8 μm [ 23 ]; contact angle = 0° [ 24 ]) in the control group, CMI IS-III Active implant (Neobiotech Co., Seoul, Korea; Ra = approximately 3.5 μm; contact angle = 109.2° [ 20 ]) in the experimental group 1, and CMI IS-III HActive implant (Neobiotech Co., Seoul, Korea; Ra = approximately 3.5 μm; contact angle = approximately 4° [ 20 ]) in experiment group 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation